1998
DOI: 10.1074/jbc.273.44.28773
|View full text |Cite
|
Sign up to set email alerts
|

3′-Phosphorylated Nucleotides Are Tight Binding Inhibitors of Nucleoside Diphosphate Kinase Activity

Abstract: The sulfate group is directed toward the protein surface. PAPS will be useful for the design of high affinity drugs targeted to NDP kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…As reflected in the IC 50 (the concentration of inhibitor resulting in 50% inhibition) values, AMP and UDP were potent inhibitors compared with cyclic AMP. However, unlike other NdKs (44,45), the phosphotransfer activity of mNdK (Table I) was not affected by either cromoglycate or 3Ј-phosphate nucleotides (PAP or PAPS). Thus our results highlighted the distinction in the behavior of mNdK compared with other bacterial homologues.…”
Section: Resultsmentioning
confidence: 75%
“…As reflected in the IC 50 (the concentration of inhibitor resulting in 50% inhibition) values, AMP and UDP were potent inhibitors compared with cyclic AMP. However, unlike other NdKs (44,45), the phosphotransfer activity of mNdK (Table I) was not affected by either cromoglycate or 3Ј-phosphate nucleotides (PAP or PAPS). Thus our results highlighted the distinction in the behavior of mNdK compared with other bacterial homologues.…”
Section: Resultsmentioning
confidence: 75%
“…5). Because pAp acts as a competitive inhibitor of several enzymes (31,49,50), high concentrations of pAp are toxic for cells. RecJ-like proteins may degrade pAp to control the concentration in bacteria and archaea that do not have CysQ (30 -34) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The main enzyme involved in the phosphorylation of TDP to TTP is NDPK. However, the phosphorylation efficiencies of NDPK for AZTDP and D4TDP are at least 10 4 -fold less and 10 3 -fold less than those for naturally occurring TDP, respectively (40)(41)(42). Hsu et al observed that 4Ј-Ed4TDP can also be phosphorylated by PGK and pyruvate kinase (19).…”
Section: Discussionmentioning
confidence: 99%